Survival of infants born at periviable gestation: The US national database - Ibrahim Qattea; Mohsen A.A. Farghaly; Mohammad O. Kattea; Nibras Abdula; Mohamed A. Mohamed; Hany Aly (Elsevier, 2022)
Summary: Background: Substantial differences exist in the approach to resuscitating infants born at periviable gestation. Evaluation of current survival may help guide prenatal counselling and provide accurate expectations of clinical outcomes. We aimed to assess the US national survival trends in periviable infants born at gestational age (GA) ≤24 weeks. Methods: We used de-identified patient data obtained from the US Healthcare Cost and Utilization Project (HCUP) from 2007 to 2018. All infants with documented GA ≤24 weeks were included. The Cochran-Armitage test was used for trend analyses. Regression analyses were conducted for variables associated with survival. Findings: A total of 44,628,827 infant records were identified with 124,345 (0.28%) infants born ≤24 weeks; of those, 77,050 infants <24 weeks and 47,295 infants had completed 24 weeks. Survival rates for infants <24 weeks and with completed 24 weeks were 15.4% and 71.6%, respectively, with higher survival over the years (Z = 9.438, P<0.001 & Z = 3.30, P<0.001, respectively). Survival was lower in males compared to females (aOR = 0.96, CI: 0.93-0.99 & aOR = 0.94, CI: 0.92-0.96, respectively) and with private insurance compared to public insurance (aOR = 0.74, CI: 0.71-0.77 & aOR = 0.67, CI: 0.65-0.69, respectively). Survival was higher when birth weight was >500 g compared to ≤500 g (aOR = 4.62, CI:3.23-5.02 & aOR = 5.44, CI: 4.59-5.84, respectively). Black (aOR = 1.33, CI: 1.31-1.36 & aOR = 1.24, CI: 1.20-1.32, respectively) and Hispanic (aOR = 1.29, CI: 1.27-1.32 & aOR = 1.27, CI: 1.22-1.30, respectively) had higher survival than White. Interpretation: There is a national increase in survival over the years in infants born at periviable GA. BW >500 is associated with >4 folds higher survival compared to ≤500 g. The results of this study should be cautiously interpreted as long-term outcomes are unknown Funding: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors.